Cooperative Learning Management Using STAD Technique Together with KWDL Technique on Learning Achievement and Mathematical Problem Solving Ability of Grade 3 Students - Chamnanvait, Monsicha; Choorak, Juraisiri (Suan Dusit Graduate School Academic Journal, 2024)
The objectives of this research were: 1) to compare the mathematical learning achievements of grade 3 students between before and after applying cooperative learning management using STAD technique together with KWDL technique, 2) to compare mathematical problem solving ability of grade 3 students before and after applying cooperative learning management using STAD technique together with KWDL technique, and 3) to study the grade 3 students’ satisfaction on learning through cooperative learning management using STAD technique together with KWDL technique. The sample were 23 grade 3 students in semester 2 of academic year 2022 at Bankonklan School, Thung Wa District, Satun Province. Multi-stage random sampling was employed. The research instruments included: 1) lesson plans, 2) an achievement test, 3) a mathematical problem solving test, and 4) a satisfaction questionnaire. The data were analyzed using median, quartile deviation, and Wilcoxon test. The data analysis revealed that: 1) the students’ mathematical learning achievement after applying cooperative learning management using STAD technique together with KWDL technique was higher than the pre-test at the statistical significance level of .05, 2) the students’ mathematical problem solving ability was higher than the pre-test at the statistical significance level of .05, and 3) the students’ satisfaction on learning through cooperative learning management using STAD technique together with KWDL technique was at the highest level.